Splitting with Different Growth Rates for Linear Discrete-time Skew-evolution Semiflows in Banach Spaces - Borlea Diana (Annals of the West University of Timisoara: Mathematics and Computer Science, 2018)
In this paper we intend to study three concepts of (h, k)-splitting for skew-evolution semiflows, which model discrete-time variational systems in Banach spaces. We also aim to give connections between them, emphasized by counterexamples and we propose an open problem.